Advanced Hydrogen-Bromine Flow Batteries with Improved Efficiency, Durability and Cost. Issue 1 (1st September 2015) - Lin, G.; Chong, P.Y.; Yarlagadda, V.; Nguyen, T.V.; Wycisk, R. J.; Pintauro, P. N.; Bates, M.; Mukerjee, S.; Tucker, M. C.; Weber, A. Z.
Abstract : The hydrogen/bromine flow battery is a promising candidate for large-scale energy storage due to fast kinetics, highly reversible reactions and low chemical costs. However, today's conventional hydrogen/bromine flow batteries use membrane materials (such as Nafion), platinum catalysts, and carbon-paper electrode materials that are expensive. In addition, platinum catalysts can be poisoned and corroded when exposed to HBr and Br2, compromising system lifetime. To reduce the cost and increase the durability of H2 /Br2 flow batteries, new materials are developed. The new Nafion/ polyvinylidene fluoride electrospun composite membranes have high perm-selectivity at a fraction of the cost of Nafion membranes; the new nitrogen-functionalized platinum-iridium catalyst possesses excellent activity and durability in HBr/Br2 environment; and the new carbon-nanotube-based Br2 electrodes can achieve equal or better performance with less materials when compared to baseline electrode materials. Preliminary cost analysis shows that the new materials reduce H2 /Br2 flow-battery energy-storage system stack and system costs significantly. The resulting advanced H2 /Br2 flow batteries offer high power, high efficiency, substantially increased durability, and expected reduced cost.